A standard operating procedure for online writing assessment using automatic summarizer in online learning environment - Mohd. Yusoff, Nuur Fatihah (2014)
Automatic Summarizers are expected to produce a condense input, retained important content and presenting coherent information. It is a method using in written assessment to solve human weakness in online learning. Combining the assessment technique with canvas as a Learning Management System can provide a new alternatives as referred in literature review to represent an automated writing assessment by implementing the alternatives in Standard Operating Procedure (SOP). This study found two (2) main problems in the current Standard Operating Procedure which is time consuming and non integrity students score produce by human rater. To solve these problems, this study proposed a new Standard Operating Procedure with additional assessment technique in composing model answers automatically and generates score using canvas also automatically. Meanwhile, to measure the effectiveness of proposed Standard Operating Procedure was constructing based on Module Multimedia in Kolej Teknologi Darulnaim. The result produced by the proposed Standard Operating Procedure has outperformed and has the capability in reduce the time and satisfy the users. Besides, by using proposed Standard Operating Procedure, the goal of assessment which is to determine if learning objectives have been accomplished